Ethylene Induces a Rapid Degradation of Petal Anthocyanins in Cut Vanda ‘Sansai Blue’ Orchid Flowers - Khunmuang, Sudarat; Kanlayanarat, Sirichai; Wongs-Aree, Chalermchai; Meir, Shimon; Philosoph-Hadas, Sonia; Oren-Shamir, Michal; Ovadia, Rinat; Buanong, Mantana (Frontiers in Plant Science, 2019)
Ethylene plays a major role in the regulation of flower senescence, including in the ethylene-sensitive Vanda ‘Sansai Blue’ orchid flowers. This cut flower is popular in Thailand due to its light blue big size florets possessing a beautiful shape pattern. In the present study, we further examined the rapid ethylene-induced process of active anthocyanin degradation in cut Vanda ‘Sansai Blue’ flowers, which occurred much before detection of other typical senescence-related symptoms. For this purpose, the cut inflorescences were exposed to air (control), 1 or 10 µL L-1 ethylene for 24 h, or to 0.2 µL L-1 1-methylcyclopropene (1-MCP) for 6 h followed by 10 µL L-1 ethylene for 24 h at 21 °C, and the effects of these treatments on various parameters were assayed. While the fading-induced effect of ethylene was not concentration-dependent in this range, the ethylene treatment significantly reduced the flower vase life in a concentration-dependent manner, further confirming the separation of the bleaching process from senescence. Exposure of the inflorescences to 1-MCP pre-treatment followed by 10 µL L-1 ethylene, recovered both inflorescence color and anthocyanin content to control levels. Quantification of total anthocyanin content, performed by HPLC analysis on the basis of cyanidin-3-glocuside equivalents, showed that ethylene reduced and 1-MCP recovered the anthocyanins profile in non-hydrolyzed anthocyanin samples of Vanda ‘Sansai Blue’ florets, assayed at half bloom and bloom developmental stages. The results showed that the ethylene-induced color fading, observed immediately after treatment, resulted from a significant reduction in the levels of the two main anthocyanidins, cyanidin and delphinidin, as well as of other anthocyanidins present in low abundance, but not from changes in the levels of flavonols, such as kaempferol. This anthocyanin degradation process seems to operate via ethylene-increased peroxidase activity, detected at the bud stage. Taken together, our results suggest that the ethylene-induced rapid color bleaching in petals of cut Vanda ‘Sansai Blue’ flowers is an outcome of in-planta anthocyanin degradation, partially mediated by increased peroxidase activity, and proceeds independently of the flower senescence process.